Accuracy of pulse rate derived from 24-h ambulatory blood pressure monitoring compared with heart rate from 24-h Holter-ECG. Issue 12 (December 2020) - Lauder, Lucas; Scholz, Sean S.; Ewen, Sebastian; Lettner, Christine; Ukena, Christian; Böhm, Michael; Mahfoud, Felix
Abstract : Background: Resting heart rate (HR) associates with cardiovascular outcomes in the general population and in patients with hypertension and heart failure. The accuracy of pulse rate acquired by 24-h ambulatory blood pressure monitoring (ABPM-PR) in comparison with Holter-ECG HR (Holter-HR) is unknown. Objective: We aimed at investigating the accuracy of ABPM-PR when compared with Holter-HR. Methods and results: The current study included 1500 patients of a general cardiology outpatient unit undergoing simultaneous Holter and ABPM recordings. ABPM-PR differed marginally from Holter-HR by 0.55 bpm for 24-h average [95% confidence interval (CI): 0.37–0.73, P  < 0.001], 1.27 bpm for daytime (95% CI: −0.98–1.56, P  < 0.001) and 0.63 bpm for night-time (95% CI: 0.40–0.86 bpm; P  < 0.001). The absolute delta between 24-h Holter-HR and ABPM-PR was less than 5 and less than 10 bpm in 1363 (91%) and 1458 (97%) patients, respectively. 24-h ABPM-PR more commonly underestimated than overestimated (7 versus 2%) 24-h Holter-HR by at least 5 bpm. The mean difference between Holter-HR and ABPM-PR was higher (+1.9 bpm; 95% CI: 0.9–3.0; P  < 0.001) in patients with than without atrial fibrillation. There was no significant difference between Holter-HR and ABPM-PR in patients without supraventricular or ventricular extrasystoles (both P  ≥ 0.750). Conclusion: ABPM-PR did not differ clinically meaningful from Holter-HR recordings in most patients and might be useful for risk prediction in hypertension. Abstract : Supplemental Digital Content is available in the text